2013
DOI: 10.1371/journal.pone.0065384
|View full text |Cite
|
Sign up to set email alerts
|

Structurally Designed Attenuated Subunit Vaccines for S. aureus LukS-PV and LukF-PV Confer Protection in a Mouse Bacteremia Model

Abstract: Previous efforts towards S. aureus vaccine development have largely focused on cell surface antigens to induce opsonophagocytic killing aimed at providing sterile immunity, a concept successfully applied to other Gram-positive pathogens such as Streptococcus pneumoniae. However, these approaches have largely failed, possibly in part due to the remarkable diversity of the staphylococcal virulence factors such as secreted immunosuppressive and tissue destructive toxins. S. aureus produces several pore-forming to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 43 publications
2
67
0
Order By: Relevance
“…Similarly, the administration of anti-PVL antibodies to the eyes of S. aureusinfected mice using a keratitis model demonstrated increased efficacy for the resolution of CA-MRSA (327). An additional study showed that immunization of mice with rationally designed mutants of PVL leads to significantly improved outcomes in a lethal systemic infection model, although the protection observed in this model is likely due to the broadly neutralizing capacity of the sera (lytic factors other than PVL were blocked by sera obtained from PVL-immunized animals) (328). Currently, it is difficult to reconcile the conflicting evidence both in favor of and against leucocidin immunization strategies as viable therapeutic options.…”
Section: Targeting Of Leucocidins As a Therapeutic Modalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the administration of anti-PVL antibodies to the eyes of S. aureusinfected mice using a keratitis model demonstrated increased efficacy for the resolution of CA-MRSA (327). An additional study showed that immunization of mice with rationally designed mutants of PVL leads to significantly improved outcomes in a lethal systemic infection model, although the protection observed in this model is likely due to the broadly neutralizing capacity of the sera (lytic factors other than PVL were blocked by sera obtained from PVL-immunized animals) (328). Currently, it is difficult to reconcile the conflicting evidence both in favor of and against leucocidin immunization strategies as viable therapeutic options.…”
Section: Targeting Of Leucocidins As a Therapeutic Modalitymentioning
confidence: 99%
“…Thus, not only are anti-PVL antibodies capable of reducing PVL-induced inflammation in in vivo rabbit models, it is also possible to generate antibody molecules that neutralize more than one leucocidin pair. Work by Karauzum and colleagues also demonstrated that the generation of broadly neutralizing antibodies after immunization with PVL can have dramatic effects on pathogenic outcomes using a lethal murine systemic infection model (328). It is likely that antibodies with cross-neutralizing capabilities such as these will prove far more efficacious, highlighting promise toward the development of antitoxin molecules that may be able to target multiple toxins at the same time.…”
Section: Targeting Of Leucocidins As a Therapeutic Modalitymentioning
confidence: 99%
“…19 a-toxin and Panton-Valentine leukocidin (PVL) are 2 toxins of interest for a toxoid based approach that have shown efficacy in animal models. [20][21][22] a-toxin is a highly conserved toxin that causes tissue barrier disruption at host interfaces lined by epithelial or endothelial cells, and undermines the host immune response. 23 Reduced skin lesion size and dermonecrosis were observed in mice immunized with a nontoxigenic form of a-toxin, following infection with USA300.…”
Section: Introductionmentioning
confidence: 99%
“…34 Protection against USA300 sepsis was demonstrated in a murine model using a vaccine composed of highly attenuated forms of PVL sub-units (rLukS-PV or rLukF-PV). 21 …”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that the presence of higher titers of antiexotoxin antibodies at the time of sepsis is associated with improved outcomes in patients with invasive S. aureus infection (7). We have previously shown that a toxoid vaccine for S. aureus poreforming toxins, such as alpha-hemolysin (Hla) and leukocidins, can provide protection against S. aureus infection in mice (29,30). A multivalent toxoid vaccine can also be combined with surface antigens to induce both toxin neutralization and opsonophagocytic activity.…”
Section: Discussionmentioning
confidence: 99%